Determinan Faktor Struktur Modal pada Perusahaan Properti dan Real Estate yang Terdaftar di Bursa Efek Indonesia pada Tahun 2013-2018 - Mohammad Zidni Rizky; R. Aditya Kristamtomo Putra (e-Journal Ekonomi Bisnis dan Akuntansi, 2020)
The aim of this study was to analyze the determinant factors of capital structure on property and real estate companies listed in Indonesia Stock Exchange in 2013-2018. The independent variables used in this study were assets structure, profitability, firm growth, firm size, and liquidity, whereas the dependent variable was capital structure. This study used purposive sampling so there were 29 companies being analyzed. The data was analyzed using panel data multiple linear regression method with Random-effects Model approach. This study found that simultaneously, the assets structure, profitability, firm growth, firm size, and liquidity could significantly affecting the capital structure of the companies. Partially, the assets structure and liquiditty negative and insingificant effect, profitabillity has negative and signficant effect, firm growth has positive and significant efect, and firm size has positive and insignificant effect.